Gowaslu sebagai Electoral Technology: Keterlibatan Publik dalam Pengawasan Partisipatif Berbasis Daring - Mahpudin Mahpudin (Badan Pengawas Pemilihan Umum, 2021)
The Gowaslu application is an election technology that exists to expand public involvement in online participatory surveillance. Public involvement in election supervision is important amid the limitations of Bawaslu in supervising the practice of election violations and fraud. This article attempts to capture how effective the Gowaslu application is in strengthening public involvement in participatory monitoring. The research method used is qualitative with a descriptive analysis approach. Data collection is secondary through a search of a number of literatures. The findings of this research reveal that the Gowaslu application is an innovation by Bawaslu by utilizing digital technology in the context of election monitoring. However, this application has not been substantively effective in expanding public involvement in participatory monitoring. The problems found are that the follow-up reports have not been submitted openly, the content is not interesting and not interactive because it is only one way, there is no voter education to ensure the quality of the report. In addition, the Gowaslu application has not been used massively by the public, referring to the very small number of application users and reports of alleged election violations which are still low compared to Bawaslu's findings